ANALISIS VEGETASI DALAM UPAYA PENGEMBANGAN WISATA DI TAMAN WISATA ALAM PUNTI KAYU PALEMBANG PROVINSI SUMATERA SELATAN - Akbar Rulianto; Afif Bintoro; Gunadi Djoko Winarno; Rahmat Safe'i (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Punti Kayu Natural Tourism Park is a conservation forest contained in Palembang with an area of 50 hectares. Conservation forest utilization as a natural tourism park has a fantastic tourism development potential. Considering this matter, it is necessary to research about vegetation analysis at Punti Kayu nature tourism park for tourism development at Punti Kayu Palembang. The purpose of this research is to know the composition and structure of tree vegetation at TWA Punti Kayu Palembang. The research was conducted from April to June 2017. The method used in this research is Simple Random Sampling with 63 plot total sample.The results of this study obtained 24 tree species consisting of 949 tree phases, 114 pole phases, 141 sappling phases, and 375 phases of seedlings.Tree phases was dominated by Pinus Spesies with total 750 trees (INP 212,65%), in the pole phase, sapplings phase and seedling phase were dominated by Talok with total 25 poles (INP 57,96%), 17 sapplings (INP 39.89%) and 60 seedlings (INP 29.51%), The level of diversity of tree species and seedlings included in the low category, the tree of 0.493 and the seedlings of 0.824. One characteristic of good vegetation is the high level of species diversity. according to Kristinawanti et al (2013) good tree vegetation will have a positive impact on increasing tourist visits The results of this research can be used to support tourism in Punti Kayu Nature Tourism Park because it can be used as a reference to assess the management of Punti Kayu Nature Tourism Park.